Anxiety and depression information for teens : basic health information on anxiety and depression in teens and its various types, the causes, risk factors, diagnosis, treatments, and coping methods including information about managing anxiety and depression with the help of family, friends, pets, and relaxation techniques - 4 0 16; (Editor of health information), Hayes, Kevin; 5 (Detroit, MI : Omnigraphics, Inc., 2020)
Provides basic health information on anxiety and depression in teens and its various types, causes, risk factors, diagnosis, treatments, and coping methods. Includes an index, and a directory of organizations for additional help and information--
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; Anxiety in adolescence;Depression in adolescence -- 20 -- Juvenile literature.;Juvenile literature; 20; 2